INFLUENCE OF SOWING TIME ON PRODUCTIVITY OF SMOOTH BROME GRASS IN THE FOREST-STEPPE OF UKRAINE - Marinich, L. H.; Antonets, O. A. (Scientific Progress & Innovations, 2021)
Perennial grasses are the main fodder crops for hayland and pasture use. Their area of extending is quite large: they are spread from the tropics to the extreme northern regions. Their role is significant in the farm- ing system: they protect the soil from water and wind erosion, enrich it with organic matter, improve the physical and mechanical properties of the soil and precipitation infiltration.The group of forage grasses includes more than 600 species of plants, but smooth brome grass has the greatest forage value has, it is used for green fodder, silage, haylage and grass meal. Under favorable growing conditions, modern zoned varieties of this plant are able to form biological seed yield of up to 0.6–0.8 t/ha, 50.0 t/ha of green mass, and 20.0 t/ha of hay. But obtaining such high and stable yields requires compliance with all agro-technical operations. The purpose of the research was to determine the sowing time, affecting the formation of seed and feed productivity of smooth brome grass. Field and quantitative methods, the method of test sheaf, weight, and statistical methods were used in the proces of research. The high fodder value of smooth brome grass can be explained by the fact that it has a significant number of vegetative shoots with more leaves than on generative ones. In addition, the leaves, especially on vegetative shoots, contain more nutrients. The smallest number of vegetatively elongated shoots was formed by plants of Poltavsky 5 and Poltavsky 52 varieties under the conditions of autumn sowing period. The largest number of vegetatively elongated shoots in these varieties was observed at spring sowing time. The optimal sowing season for obtaining high seed yields for smooth brome grass of Poltavsky 5 and Poltavsky 52 varieties is summer. The optimal sowing time for obtaining high yields of green mass for smooth brome grass of Poltavsky 5 and Poltavsky 52 varieties is spring. Spring sowing time is also the optimal sowing period for obtaining high yields of dry matter for smooth brome grass of Poltavsky 5 and Poltavsky 52 varieties.